A Robust Iris Localization and Texture Extraction Scheme for Iris Authentication Systems - Hayder Najm; Mohammed, Bahaa Kareem; Naman, Hala A.; Bazar, Hussein Al; Mahdi, Mohammed Salih; Abdulhussien, Wijdan Rashid (Journal of Advanced Research Design, 2025)
Biometrics systems accurately identify and distinguish individuals based on their characteristics. Due to the high accuracy and stability, iris has been widely used in the authentication process of authorized persons. One of the most important processes in developing an iris recognition system is iris segmentation since it has a substantial impact on the accuracy of iris matching.